Empowering Women through Microfinance in Nepal - Sharma, Deergh Narayan (Nepalese Journal of Management Science and Research, 2023)
The research article tried to highlight the impact of microfinance on women’s empowerment in the context of Nepal and the impact of COVID-19 on the business and economic sustainability of microfinance in Nepal. In this paper, the history of microfinance and the link between microfinance and women’s empowerment has been discussed comprehensively. Apart from that in the wider phenomenon of women empowerment, the theories on woman empowerment have been explained. The research gap here is stated as the effect of COVID-19 on these two topic variables. The methodology here was a descriptive design and conceptual framework to discuss the basic links between these two research variables. The challenges of human empowerment in Nepal, the influence of microfinancing in increasing the living standard of women, the economic effects of COVID-19 on females and the performance of MSI with rising Covid 19 effects have been discussed.